Influence of Winter Subsurface on the Following Summer Variability in Northern California Current System. Issue 12 (21st December 2022) - Ray, Sulagna; Bond, Nicholas; Siedlecki, Samantha; Hermann, Albert J.
Abstract: Temperature variations in the North and tropical Pacific contribute to the predictability of temperatures along the 26.4 σ isopycnal layer off the Northern California Current System (N‐CCS). Monthly temperature variations at this depth in the N‐CCS are related to a linear combination of factors, including North Pacific spice anomalies, and the PDO and ENSO climate indices. However, the mechanisms for seasonal predictability of subsurface temperatures, are not well explored. While wind and buoyancy driven deep winter mixing influence subsurface temperatures during the following summer in the deep basin of the North Pacific, a coupled atmosphere‐ocean reanalysis (the CFSR) reveals that winter prior surface temperatures explain only 25% of the summer subsurface temperatures in the N‐CCS. A heat budget of the intermediate layer between a temporally varying mixed layer and the 26.4 σ level is diagnosed here to explore the possible role of oceanic advection in explaining the remaining variance. Warmer waters from the south near the coast drive temperature changes in ENSO‐neutral winters, thereby preconditioning temperatures for the following summer. During ENSO winters, isopycnal variations associated with propagating coastal kelvin waves and other sources of heaving, along with anomalous alongshore currents, drive convergence/divergence of the advective fluxes, thereby reducing the local memory of the winter subsurface temperatures. Variations in winter advection could account for almost 36% of the summer subsurface temperature variability in the N‐CCS; this exceeds the portion explained by the heat fluxes associated with deep winter mixing. Plain Language Summary: Summer upwelling brings colder waters onto the shelf and signifies the beginning to the highly productive season for fisheries and ecosystems off the Northern California Current System (N‐CCS). Along the bottom, many important marine species reside with associated thermal tolerances that have been exceeded during recent warm events. Advanced knowledge of these events on seasonal or longer timescales aids in fisheries management. Understanding processes driving seasonal and interannual variations of subsurface temperature conditions is vital to developing prognostic skill. Regional climate indices, like the Pacific Decadal Oscillation and El Niño and Southern Oscillation (ENSO), are correlated with subsurface temperature variability in the N‐CCS, yet the actual drivers of seasonal subsurface temperatures are not well explored. Here we show that summer temperatures are related to the conditions in the winter prior and that the strength of this connection depends on whether or not the winter features an ENSO event. Along‐shore currents near the coast during non‐ENSO winters are responsible for much of the preconditioning of the subsurface temperatures observed the following summer. During ENSO winters, this preconditioning is weaker, because subsurface variations associated with isopycnal heave and coastally trapped waves, along with changes in poleward currents, influence the subsurface summer temperatures. Key Points: Northern CCS summer temperatures are more strongly correlated with winter prior subsurface temperatures during ENSO‐neutral years Changes in isopycnals and currents during ENSO reduce the effects of persistence in the subsurface temperatures found for ENSO‐neutral years Pre‐conditioning of the winter subsurface during ENSO‐neutral years is a source of predictability for the following summer temperatures